Keanekaragaman Jamur Makroskopis di Hutan Gambut Arboretum Nyaru Menteng Kalimantan Tengah - Desimaria Panjaitan; Frans Grovy Naibaho; Retno Agnestisia; Ivan Permana Putra (Konservasi Hayati, 2023)
Information on macroscopic fungi from Central Kalimantan is still limited compared to other regions in Indonesia. Arboretum Nyaru Menteng, a conservation area located in Central Kalimantan, poses many macrofungi due to its favorable environmental conditions that support the growth of various types of macrofungi. However, the diversity of macroscopic fungi from Arboretum Nyaru Menteng has never been reported. Thus, the current works aimed to provide initial information on the diversity of macroscopic fungi in this conservation area. The exploration was done using the opportunistic sampling method. Fruiting bodies were documented, collected, and identified based on macroscopic characteristics. Four environmental microclimate variables were measured in four random sampling locations: temperature, light intensity, air humidity, and soil acidity. The results confirmed that there were 27 species of macrofungi belonging to 18 genera and 14 families. Polyporaceae was the most dominant family found in this research. Most fungi grew on a dead log while the others were recognized as mycorrhizal fungi and parasites on plants. The environmental measurements showed that Arboretum Nyaru Menteng has an optimal habitat for recorded fungi growth. The record of macrofungi diversity in this research contributes to Indonesia mycoflora, particularly from Central Kalimantan.